Association of Physical Activity and Cognitive Activity With Disability: A 2-Year Prospective Cohort Study. Issue 8 (4th April 2020) - Kurita, Satoshi; Doi, Takehiko; Tsutsumimoto, Kota; Nakakubo, Sho; Kim, Minji; Ishii, Hideaki; Shimada, Hiroyuki
Abstract: Objective: Engaging in physical activity (PA) and/or cognitive activity (CA) retains function in older adults, but whether the combination of these activities is associated with disability onset is still unknown. This study aimed to examine the prospective association of PA and/or CA with disability onset in older adults. Methods: This was an ongoing prospective community-based cohort study. Data collection was conducted through a health check. An analyzable sample of 2668 participants (mean age = 75.5 years; 51.6% female) were categorized into 4 groups based on quartile 1 (low) and 2 to 4 (high) values of accelerometer-measured moderate-to-vigorous PA and CA scale scores based on the frequency of 6 activities including reading, writing for pleasure, doing crossword puzzles, and playing board games or cards. Disability onset was monitored through long-term care insurance certification for at least 2 years. Results: A log-rank test showed significantly lower incidence of disability in the high PA and low CA group and the high PA and high CA group compared with the low PA and low CA group. Cox-proportional hazards models (referring to the low PA and low CA group) showed that only the high PA and high CA group was significantly associated with a lowered hazard ratio for disability onset (0.51; 95% CI = 0.29–0.90) after adjusting for covariates. Conclusions: Engaging in both PA and CA is effective for reducing risk of disability onset, but engaging in either PA or CA is not effective. Impact: Physical therapists can be guided by this research to design intervention strategies for people at risk of disability.